Photochemical Cross-Couplings using Semiconducting Materials - Pieber, Bartholomäus (Synlett, 2025)
In this personal account, I describe the work performed in my research group on the development of methods that harness heterogeneous photocatalysts for light-mediated nickel-catalyzed cross-couplings. This includes catalytic systems using carbon nitride materials, dye-sensitized TiO₂, covalent organic frameworks (COFs), and conjugated polymers. The rationale behind the selection of materials and how their use led to the identification of catalyst deactivation, structure–activity relationships, and future opportunities is discussed.
Keywords: Photocatalysis; Heterogeneous catalysis; Semiconductors; Nickel catalysis; Cross-couplings